How to cook : building blocks and 100 simple recipes for a lifetime of meals - Acheson, Hugh (Clarkson Potter/Publishers, 2020)
"An empowering collection of impressive recipes that will teach young adults and kitchen novices all the skills they need to cook for themselves--from a James Beard Award-winning chef and author"--